Andalusia dalam Perspektif Sejarah Kritis: Menelaah Dinamika Politik, Intelektual, dan Kemasyarakatan Islam di Spanyol - Fatimah Fatimah; Tegar Hanif; Kholid Mawardi (TSAQOFAH, 2026)
The study of Islamic civilization in Spain is important for understanding the dynamics of Andalusia’s development, glory, and decline more comprehensively through the interconnection of political, intellectual, and social aspects. This study aims to analyze the political, intellectual, and social dynamics of Islam in Spain through a critical historical perspective in order to understand the factors that influenced the development of Andalusian civilization. This study used a qualitative approach with a library research design. Data were obtained through documentation studies of various scholarly sources, including books, journal articles, and relevant academic documents, then analyzed using content analysis techniques through the stages of data organization, interpretation, and synthesis. The results of the study show that the advancement of Islamic civilization in Andalusia was supported by political stability, the development of scholarly traditions, and a society capable of managing diversity in a relatively harmonious manner. Conversely, the weakening of political unity, the decline of intellectual activity, and the reduction of social cohesion contributed to the decline of this civilization. The conclusion of the study affirms that the development of a civilization is the result of multidimensional interaction among political, intellectual, and social factors, and therefore cannot be explained through a single dimension alone. The implications of this study contribute to the development of Islamic historical studies through a critical historical approach and affirm the importance of governmental stability, the strengthening of scholarly culture, and the management of social diversity in supporting the sustainability of civilization.